The new small person - Child, Lauren (Somerville, Massachusetts : Candlewick Press, 2015)
Elmore Green likes being an only child, so when his parents bring a new small person, his baby brother, into the house he is not pleased and does his best to keep the new small person out of his life.
Keywords: Brothers -- Juvenile fiction; African American boys -- Juvenile fiction; Jealousy in children -- Juvenile fiction